DPP10 is a new regulator of Nav1.5 channels in human heart. (1st June 2019) - Belau, Fabian; Metzner, Katharina; Christ, Torsten; Ravens, Ursula; Schaefer, Michael; Künzel, Stephan; Li, Wener; Wettwer, Erich; Dobrev, Dobromir; El-Armouche, Ali; Kämmerer, Susanne
Abstract: Background: Cardiac accessory β-subunits are part of macromolecular Nav1.5 channel complexes modulating biophysical properties and contributing to arrhythmias. Recent studies demonstrated the structural interaction between β-subunits of Na + (Nav1.5) and K + (Kv4.3) channels. Here, we identified the dipeptidyl peptidase-like protein-10 (DPP10), which is known to modulate Kv4.3-current kinetics, as a new regulator of Nav1.5 channels. Methods: We assessed DPP10 expression in the healthy and diseased human heart and we studied the functional effects of DPP10 on the Na + current in isolated rat cardiomyocytes expressing DPP10 after adenoviral gene-transfer (DPP10ad). Results: DPP10 mRNA and proteins were detected in human ventricle, with higher levels in patients with heart failure. In rat cardiomyocytes, DPP10ad significantly reduced upstroke velocity of action potentials indicating reduction in Na + -current density. DPP10 significantly shifted the voltage-dependent Na + channel activation and inactivation curve to more positive potentials, resulting in greater availability of Na + channels for activation, along with increasing window Na + current. In addition, time-to-peak Na + current was reduced, whereas time course of recovery from inactivation was significantly accelerated by DPP10ad. DPP10 co-immunoprecipitated with Nav1.5 channels in human ventricles, confirming their physical interaction. Conclusion: We provide first evidence that DPP10 interacts with Nav1.5 channels, linking Na + - and K + -channel complexes in the heart. Our data suggest that increased ventricular DPP10 expression in heart failure might promote arrhythmias by decreasing peak Na + current, while increasing window Na + current and channel re-openings due to accelerated recovery from inactivation. Highlights: Accessory β-subunits associate with the depolarizing Nav1.5 channel and the repolarizing Kv4.3 channel in human heart. We discovered DPP10 as a new regulator of Nav1.5 channels by co-immunoprecipitation in human heart. DPP10 altered voltage-dependence of Na + current and upstroke velocity of action potential in rat epicardial cardiomyocytes. DPP10 represents a novel functional link between the cardiac Na + and K + channels. Being upregulated in heart failure, DPP10 might contribute to the development of cardiac arrhythmias.